Mutant botrocetin‐2 inhibits von Willebrand factor‐induced platelet agglutination. (14th February 2017) - Matsui, T.; Hori, A.; Hamako, J.; Matsushita, F.; Ozeki, Y.; Sakurai, Y.; Hayakawa, M.; Matsumoto, M.; Fujimura, Y.
Abstract : Essentials Botrocetin‐2 (Bot2) binds to von Willebrand factor (VWF) and induces platelet agglutination. We identified Bot2 residues that are required for binding to VWF and glycoprotein (GP) Ib. We produced a mutant Bot2 that binds to VWF but inhibits platelet agglutination. Mutant Bot2 could be used as a potential anti‐thrombotic reagent to block VWF–GPIb interaction. Summary: Background: Botrocetin‐2 (Bot2) is a botrocetin‐like protein composed of α and β subunits that have been cloned from the snake Bothrops jararaca . Bot2 binds specifically to von Willebrand factor (VWF), and the complex induces glycoprotein (GP) Ib‐dependent platelet agglutination. Objectives: To exploit Bot2's VWF‐binding capacity in order to attempt to create a mutant Bot2 that binds to VWF but inhibits platelet agglutination. Methods and Results: Several point mutations were introduced into Bot2 cDNA, and the recombinant protein (recombinant Bot2 [rBot2]) was purified on an anti‐botrocetin column. The mutant rBot2 with either Ala at Asp70 in the β subunit (Aspβ70Ala), or Argβ115Ala and Lysβ117Ala, showed reduced platelet agglutination‐inducing activity. rBot2 with Aspβ70Ala showed little binding activity towards immobilized VWF on an ELISA plate, whereas rBot2 with Argβ115Ala/Lysβ117Ala showed reduced binding activity towards GPIb (glycocalicin) after forming a complex with VWF. rBot2 point‐mutated to oppositely charged Glu at both Argβ115 and Lysβ117 showed normal binding activity towards VWF but no platelet‐agglutinating activity. Furthermore, this doubly mutated protein inhibited ristocetin‐induced or high shear stress‐induced platelet aggregation, and restrained thrombus formation under flow conditions. Conclusions: Asp70 in the β subunit of botrocetin is important for VWF binding, and Arg115 and Lys117 in the β subunit are essential for interaction with GPIb. Doubly mutated rBot2, with Argβ115Glu and Lysβ117Glu, repels GPIb and might have potential as an antithrombotic reagent that specifically blocks VWF function. This is the first report on an artificial botrocetin that can inhibit the VWF–GPIb interaction.